2022
DOI: 10.1155/2022/2266023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Zuojin Pill for the Treatment of Chronic Nonatrophic Gastritis: A Randomized Active-Controlled Clinical Trial

Abstract: Objective. Zuojin pill (ZJP) is used as the classical prescription for a wide variety of digestive diseases. However, there is a lack of direct evidence for its use in the treatment of chronic nonatrophic gastritis (CNG). In particular, there is a lack of rigorous trials of randomized controlled designs. In this study, a randomized active-controlled clinical trial was performed to verify the efficacy and safety of ZJP in detail. Methods. Patients with CNG were divided into the ZJP group and the Marzulene-S gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Huaglian (Coptidis rhizoma)–Wuzhuyu (Evodiae Fructus) is a well-known herb pair combination (HYHP) that is commonly used for the treatment of liver, gallbladder, and digestive diseases. Recent research has revealed that HYHP contains several active chemicals, including berberine and evodiamine, which have diverse pharmacological effects, such as anti-inflammatory, anti-fibrotic, barrier protection, flora regulation, and lipid-lowering properties. Zhuyu Pill (ZYP, Huanglian and Wuzhuyu in a 1:1 ratio, g/g) is a traditional HYPY formula. Previous studies have demonstrated that ZYP effectively reduces inflammation and hepatic steatosis in mice by suppressing the NLRP3 inflammasome .…”
Section: Introductionmentioning
confidence: 99%
“…Huaglian (Coptidis rhizoma)–Wuzhuyu (Evodiae Fructus) is a well-known herb pair combination (HYHP) that is commonly used for the treatment of liver, gallbladder, and digestive diseases. Recent research has revealed that HYHP contains several active chemicals, including berberine and evodiamine, which have diverse pharmacological effects, such as anti-inflammatory, anti-fibrotic, barrier protection, flora regulation, and lipid-lowering properties. Zhuyu Pill (ZYP, Huanglian and Wuzhuyu in a 1:1 ratio, g/g) is a traditional HYPY formula. Previous studies have demonstrated that ZYP effectively reduces inflammation and hepatic steatosis in mice by suppressing the NLRP3 inflammasome .…”
Section: Introductionmentioning
confidence: 99%